1996
DOI: 10.1111/j.1365-2885.1996.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of oxytetracycline, tetracycline and chlortetracycline after oral administration to fed and fasted pigs

Abstract: The disposition of oxytetracycline (OTC), tetracycline (TC) and chlortetracycline (CTC) was measured after intravenous and oral administration to pigs. Eighteen healthy pigs (six for each compound) weighing 22-43 kg received a dose of 10 mg/kg intravenously, and 45 mg/kg (OTC and TC) or 40 mg/kg (CTC) orally in both a fasted and a fed condition in a three-way crossover design. The three tetracyclines were present in plasma up to 30 hours after intravenous and after oral administration to fasted as well as fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
72
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 16 publications
(5 reference statements)
7
72
0
Order By: Relevance
“…In spite of the low bioavailability it was possible to obtain therapeutically active concentrations up to 6 hr after administration of 50 mg/kg body weight to fasted as well as fed pigs. The bioavailability of oxytetracycline, tetracycline and chlortetracycline was 3%, 18% and 11% respectively in fasted pigs versus 3%, 5% and 6% in the group of fed pigs (Nielsen & Gyrd-Hansen 1996). Based on the bioavailability and the resulting plasma concentrations it was concluded that it was not possible to obtain a therapeutically active concentration in plasma or tissues after oral administration of any of the three tetracyclines to fed or fasted pigs.…”
mentioning
confidence: 92%
“…In spite of the low bioavailability it was possible to obtain therapeutically active concentrations up to 6 hr after administration of 50 mg/kg body weight to fasted as well as fed pigs. The bioavailability of oxytetracycline, tetracycline and chlortetracycline was 3%, 18% and 11% respectively in fasted pigs versus 3%, 5% and 6% in the group of fed pigs (Nielsen & Gyrd-Hansen 1996). Based on the bioavailability and the resulting plasma concentrations it was concluded that it was not possible to obtain a therapeutically active concentration in plasma or tissues after oral administration of any of the three tetracyclines to fed or fasted pigs.…”
mentioning
confidence: 92%
“…Oxytetracycline (OTC) is an antimicrobial drug widely used in intensive farming to treat enteric and respiratory diseases [1,2]. Due to oral administration and its pharmacokinetic, OTC dosage is in the range of g kg −1 medicated feeds and it is found in animal waste at concentrations of mg kg −1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tetracyclines are excreted in active form in urine and feces (23) and can also be detected in animal manure slurry and manured soil (6,13,29). Therefore, the use of tetracyclines may exert selective pressure not only on bacteria within the intestinal system but also on bacteria in close contact with the environment of a pigsty or with animal manure.…”
mentioning
confidence: 99%